MTOR trains heightened macrophage responses. Issue 1 (January 2015) - Horng, Tiffany
<x xml:space="preserve">Abstract</x> The ability of a primary challenge to protect against secondary infection (e.g., during vaccination) independent of the adaptive immune system is mediated in part by macrophage 'training'. Two new studies show that macrophage training is associated with genome-wide epigenetic changes and is regulated by the mTOR pathway and metabolic reprogramming.